Preliminary Experiments on the Formation of Elongated Air Bubbles in Glacier Ice by Stress - Nakawo, Masayoshi; Wakahama, Gorow (Journal of Glaciology, 1981)
Abstract Biaxial compression tests on glacier ice with bubbles revealed that elongated air bubbles were developed with long axes in the direction of free expansion. The elongated bubbles were not only derived from spherical bubbles but also created by the healing of cracks that were developed during compression. Formation of elongated bubbles and foliations in natural glacier ice are discussed here in the light of results obtained experimentally.